Theoretical perspectives for the Environmental Education in high school. Theory and practice - Liliana Haydé Gutiérrez Sabogal (Corporación Universitaria Minuto de Dios, 2017)
This article exposes the background and conclusions of an Environmental Education purpose -EE- supported by theoretical models able to frame processes of teaching and learning applied to EE in the high school. All of this come from strict revision and analysis of complemented educational didactics, through the professional teaching experience. To reveal this conceptual framework, the activities are posed and developed within the Environmental School Project -ESP- of the District Education Institute -DEI- Ignacio Pescador as a mode to put into practice the analyzed theory. Thus, the results obtained validate the referential framework proposed to produce knowledge about the instructive theory - which is aimed to professional teachers who will be added to the teaching process of EE into the high school institutes- and the process of knowledge creation in the student body.